Change-of-direction deficit vs. deceleration deficit: A comparison of limb dominance and inter-limb asymmetry between forwards and backs in elite male rugby union players - Bishop, C.; Clarke, R.; Freitas, T. T.; Arruda, A. F. S.; Guerriero, A.; Ramos, M. S.; Pereira, L. A.; Loturco, I. (Journal of Sports Sciences, 2021)
The aims of the present study were to: 1) determine whether limb dominance and inter-limb asymmetry were the same across both change of direction (COD) and deceleration (DEC) deficits and, 2) determine the association between the COD and DEC-deficits and other physical performance tests in elite male rugby union players. Twenty five players performed a series of bilateral jumps, linear and COD speed tests at the end of the pre-season period. COD and DEC-deficits were calculated for both left and right sides, and inter-limb asymmetry thereafter. Kappa coefficients revealed moderate levels of agreement in limb dominance between COD and DEC-deficits (Kappa = 0.41 on left; 0.48 on right). For the direction of asymmetry, perfect levels of agreement (Kappa = 1) were evident between 505 time and COD-deficit, but only moderate levels of agreement (Kappa = 0.41) between other asymmetry measures. Pearson`s r correlations showed moderate to large relationships between jumps and linear (r = -0.42 to -0.68) and COD speed (r = -0.41 to -0.58), but not with the COD-deficit (r = 0.15 to -0.31), DEC-deficit (r = 0.01 to -0.32) or asymmetry (r = 0.16 to -0.29). When analysing by playing position, backs were significantly faster than forwards over 15-m (ES = -0.86) and across all jump tests (ES = 0.86-0.94), with the exception of the squat jump. This study is the first to provide a direct comparison of the COD and DEC-deficits and highlights that limb dominance and asymmetry cannot be guaranteed between tasks.